Nurturing Self-Learning Strategies at CIEX Language Courses - Brito, Tomás; Castillo, maría (CIEX JOURNAL, 2018)
This study was carried out at a private language institution offering language courses (English and French), as well as a bachelor in arts and a master’s degree in English. Public for the language courses ranges from preschoolers to adults of any age. The researchers are interested in discovering possible associations between the students’ learning and study habits and their learning outcomes. The research is in progress, so the analysis and discussions of the most relevant concepts, theories, and fundamentals related to language learning, particularly, about self-learning strategies are presented herein. The research intends to identify, describe, and assess learners’ and teachers’ current beliefs on the issue. The need arises from the researchers’ experience in observing students’ low performance and achievement levels considering that the research group is currently taking an advanced level English course. The main research objective of the thesis, is: To learn about students’ self-study practices and those suggested by theoretical approaches to improve their learning results. The analysis of the theory was done considering the most relevant trends in the topics and subtopics of the thesis, describing, comparing, and contrasting the theorists’ points of view.